2008
DOI: 10.1523/jneurosci.0803-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Visual Motion Area MT+/V5 Responds to Auditory Motion in Human Sight-Recovery Subjects

Abstract: Using functional magnetic resonance imaging, we found that cortical visual motion area MTϩ/V5 responded to auditory motion in two rare subjects who had been blind since early childhood and whose vision was partially recovered in adulthood. Visually normal control subjects did not show similar auditory responses. These auditory responses in MTϩ were specific to motion compared with other complex auditory stimuli including frequency sweeps and speech. Thus, MTϩ developed motion-specific responses to nonvisual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
137
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(156 citation statements)
references
References 43 publications
16
137
0
2
Order By: Relevance
“…Previous behavioral research has shown that people are sensitive to echo-motion (Rosenblum et al 2000;Thaler et al 2011), and in a previous functional magnetic resonance imaging (fMRI) study, we found that echoes from moving compared with stationary surfaces elicited an increase in activation in temporal-occipital cortex in blind echolocation experts (Thaler et al 2011). Human temporal-occipital cortex harbors visual-motion area MTϩ, as well as areas sensitive to auditory source-motion (Saenz et al 2008), however. Consequently, here we addressed the question of how neural substrates of echo-motion, auditory source-motion, and visualmotion in temporal-occipital cortex are related.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…Previous behavioral research has shown that people are sensitive to echo-motion (Rosenblum et al 2000;Thaler et al 2011), and in a previous functional magnetic resonance imaging (fMRI) study, we found that echoes from moving compared with stationary surfaces elicited an increase in activation in temporal-occipital cortex in blind echolocation experts (Thaler et al 2011). Human temporal-occipital cortex harbors visual-motion area MTϩ, as well as areas sensitive to auditory source-motion (Saenz et al 2008), however. Consequently, here we addressed the question of how neural substrates of echo-motion, auditory source-motion, and visualmotion in temporal-occipital cortex are related.…”
mentioning
confidence: 57%
“…With regard to the functional properties of visual-and source-motion areas, there is an ongoing debate as to what degree visual-motion area MTϩ is sensitive to sound-motion. While some evidence supports the idea of an auditory motion response in area MTϩ (Poirier et al 2005(Poirier et al , 2006, other evidence does not (Saenz et al 2008). It has been suggested that seemingly contradictory results may be due to differences in data analysis, i.e., analysis of spatially averaged data vs. ROI analysis (Saenz et al 2008).…”
Section: Processing Of Auditory Source-motion and Visual-motion: Relamentioning
confidence: 98%
See 2 more Smart Citations
“…Alternatively, another perspective on dorsal and ventral visual processing streams rather considers them to be involved in the control of object-directed actions and object recognition, respectively (12). Interestingly, recent studies in CB have reported task-specific responses in ventral (13)(14)(15)(16) and dorsal (17)(18)(19)(20)(21)(22) occipital streams in response to "what" and "where" nonvisual processing. For example, Renier et al (22) have recently found that the middle occipital gyrus (MOG) is preferentially activated by the spatial processing of nonvisual inputs.…”
mentioning
confidence: 99%